A world transformed - Bush, George 1924-2018; Scowcroft, Brent 1925-2020 (A Borzoi book, 1998)
Former President Bush and his national security advisor, Brent Scowcroft, tell the story of tumultuous years. Here are behind-the-scenes accounts of critical meetings in the White House and of summit conferences in Europe and the United States, interspersed with excerpts from Mr. Bush's diary. We are given fresh and intriguing views of world leaders such as Mikhail Gorbachev, Boris Yeltsin, Margaret Thatcher, Helmut Kohl, and Francois Mitterrand - and witness the importance of personal relationships in diplomacy. There is the dramatic description of how President Bush put together the alliance against Saddam Hussein in the Gulf War. There are the intensive diplomatic exchanges with Beijing following the events of Tiananmen Square, and the intricate negotiations leading up to German reunification. And there is the sometimes poignant, sometimes grim portrayal of Gorbachev's final years in power.